Inside Cover: Bipolar Electrochemical Approach with a Thin Layer of Supporting Electrolyte towards the Growth of Self‐Organizing TiO2 Nanotubes (ChemElectroChem 3/2016). Issue 3 (10th February 2016) - Saqib, Muhammad; Lai, Jianping; Zhao, Jianming; Li, Suping; Xu, Guobao
Abstract : Getting organized : The Inside Cover picture shows a schematic of the bipolar electrochemical cell utilized for the preparation of self‐organized TiO2 nanotubes by using a thin layer of electrolyte and the SEM image of self‐organized TiO2 nanotubes. More details can be found in the Communication by G. Xu and co‐workers onpage 360 in Issue 3, 2016 (DOI:10.1002/celc.201500182 ).